Analysis of the development of Oil and Gas Industry in present conditions - E. I. Larionova; T. I. Chinaeva; E. P. Shpakovskaya (Статистика и экономика, 2019)
Purpose of the study. This study examines the state of companies of oil sector based on the analysis of dynamics and relationship between basic financial indicators, characterizing the activities of oil companies; it identifies factors affecting the companies’ efficiency, such as return on sales (ROS) and productivity. The work is based on dynamic, structural, correlation analysis of analytical and statistical information on processes occurring in this area of economic activity.Materials and methods. Statistical data and analytical information on oil sector companies serve as the information base of this study. Statistical methods of information analysis (comparative analysis, analysis of time series, correlation, and regression analysis) represent the methodological base of research.Results. The authors analyzed the development trends of the global and Russian oil and gas sectors. The last two decades have been marked by changes in the global oil market that were caused by fluctuations in the price of oil and oil products and with the rise and fall in the price of Brent crude oil per barrel.The paper considers dynamics of financial indicators of Russian oil companies. An analysis of the data on the revenue of the largest Russian companies in ruble and dollar terms over the last 10 years has revealed a significant difference in the dynamics of these indicators. The authors performed ROS and oil price profitability correlation as well as correlation between the price of oil, the exchange rate and the profitability of oil companies.Conclusion. The oil and gas industry is an essential sector of the economy that heavily promotes to the socio-economic development of our country. Revenues of the oil and gas sector contribute to the Russian GDP and are a major component of the budget. There are two ways to calculate revenue of oil companies – in ruble (dollar terms) and impact of RUB/USD exchange rate. The sharp changes in the exchange rate of the last decade have advanced significant changes in the revenue of Russian oil companies.In this study, the total revenue (in dollar terms) was calculated as the ratio of revenue in rubles to the average annual exchange rate of the corresponding period. In general, the disastrous results of 2015 and 2016 led to a decrease in the average growth rates of dollar and ruble revenue, as well as profit and profitability.The authors performed a correlation analysis of return on sales and oil prices, which revealed an almost total absence of correlation between these indicators. Oil prices and exchange rates have a negligible effect on the profitability of oil companies. An inverse correlation is observed between the RUB/USD pair and the oil price per barrel. It is concluded that the cost of oil and the exchange rate have little effect on the profitability of oil companies.Since the oil and gas complex makes a very significant contribution to the development of the country’s economy, it is advisable to analyze its development trends on a regular basis. Based on the results of the economic and statistical analysis of financial indicators, it is possible to identify the main development directions of the oil and gas industry, evaluate positive and negative processes, and determine further prospects.